The Kulmian letters patent of the Teutonic Order of 1233 - Pósán, László (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
This study subjects to scrutiny the articles of the Kulmian letters patent of 1233 which determined the conditions of private and public law in the would-be state of the Teutonic Order in Prussia. The Kulmer Handfeste had laid down, at the same time, the privileges facilitating planned settlement prior to the conquest of Prussian lands. This diploma ruled on the conditions pertaining to the order of succession, the size of plots, the system of field utilization, fishing and hunting rights as well as those of criminal law and court procedures. It determined the privileges as well as the obligations linked to land-grants while it also determined the conditions of providing for the sustenance of parishes, as well as the currency of the future Teutonic state.